1994
DOI: 10.1089/aid.1994.10.1259
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Apoptosis in T Cells Expressing Human T Cell Leukemia Virus Type I Tax

Abstract: This study set out to determine whether T cell dysfunction associated with HTLV-I led to increased sensitivity of infected cells to apoptosis or, owing to their potential to develop ATL, if infected cells would become resistant to this process. To test this hypothesis we utilized the monoclonal antibody anti-APO-1, which has been demonstrated to induce apoptosis in human T cells. Human T cell lines expressing HTLV-I showed reduced susceptibility to anti-APO-1-induced apoptosis despite expression of high levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
75
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 54 publications
7
75
1
Order By: Relevance
“…Although evidence suggests that Tax either induces apoptosis or sensitizes cells to apoptotic death, there are also several reports showing an inhibition of apoptosis by Tax or HTLV-1 infection (Brauweiler et al, 1997;Copeland et al, 1994;Tsukahara et al, 1999;Mulloy et al, 1998). It has been reported that apoptosis induced by UV irradiation is inhibited in HTLV-1 infected cells (Brauweiler et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although evidence suggests that Tax either induces apoptosis or sensitizes cells to apoptotic death, there are also several reports showing an inhibition of apoptosis by Tax or HTLV-1 infection (Brauweiler et al, 1997;Copeland et al, 1994;Tsukahara et al, 1999;Mulloy et al, 1998). It has been reported that apoptosis induced by UV irradiation is inhibited in HTLV-1 infected cells (Brauweiler et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…These studies con¯ict with our results however, since infected cell lines were used in those studies, the inhibition of apoptosis may not have been Taxspeci®c. Tax also inhibited apoptosis induced by anti-APO-1 treatment (Copeland et al, 1994) or IL-2 withdrawal (Tsukahara et al, 1999). Tax has been shown to repress bax expression in vitro (Brauweiler et al, 1997), activate bcl-xl expression (Tsukahara et al, 1999) and inactivate p53 function (Mulloy et al, 1998), each of which suggests a role for Tax in inhibition of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18] Such a function of Tax prompts us to investigate the transcriptional regulation of survivin in HTLV-I-infected and Taxexpressing T cells. We previously showed that IL-2-dependent CTLL-2 cell lines that express Tax are resistant to apoptosis induced in the absence of IL-2.…”
mentioning
confidence: 99%
“…It has been hypothesized that induction of apoptosis might depend on nuclear expression of the CREB-binding protein (CBP)/p300-binding domain of the HTLV-1 transactivator Tax [Nicot and Harrod, 2000]. Conversely, it has been shown that HTLV-1-expressing human T-cell lines showed reduced susceptibility to anti-Fas [Copeland et al, 1994], and to TNFa stimulation [Yang et al, 2002]. This resistance to apoptosis might be due to the activation of NF-kB via Tax protein in HTLV-1 infected cells [Kawakami et al, 1999], to Tax-induced expression of anti-apoptotic genes [Brauweiler et al, 1997;Mori et al, 2001] and should involve p21 [Kawata et al, 2003].…”
Section: Introductionmentioning
confidence: 99%